The soccer mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : A. Whitman, 1997)
The Aldens are excited to be playing in their summer soccer league, until someone begins sabotaging the teams.
550
Accelerated Reader AR
Keywords: Sports stories; Soccer stories; Soccer -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories